Development of QR Code-Based Arabic Teaching Materials for Oral Skills: A Case Study on Hobby Topics for Grade 1 Madrasah Ibtidaiyah - Mutiatunnisa, Dina; Mujahidah, Zulfa Azalia; Asrori, Imam (Al-Arabi: Jurnal Bahasa Arab dan Pengajarannya = Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2024)
The development of Science and Technology (IPTEK) demands learning activities that also involve technology. Especially now that the world of education has been filled by the Alpha generation who are very close to digital skills, so the teaching materials used must also support students to collaborate with technology. This study aims to develop teaching materials for Arabic oral proficiency grade 1 elementary school using QR Code and describe the characteristics of the product developed. This research uses a Research and Development (R&D) approach with Thiagarajand's 4D development model which has four stages, namely difine, design, development, and disseminate. The results of the development of this research are teaching materials containing QR Codes and animated images about hobbies to interpret expressions or sentences delivered. The presentation of learning activities presented is in accordance with the Learning Implementation Plan (RPP) that has been prepared. The teaching materials contain eight criteria, namely interactive and innovative, multimedia presentation, flexibility, collaborative, based on learning implementation plans, continuous, oral approach, and parental immersion.